A grading recovery method of positive and negative materials of a nickel-zinc battery, recovered regenerated materials and applications

CN122941885APending Publication Date: 2026-10-20SHENZHEN AUTOMOTIVE RES INST BEIJING INST OF TECH (SHENZHEN RES INST OF NAT ENG LAB FOR ELECTRIC VEHICLES) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611424320.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,上述有机酸浸出方案均针对单一电极材料,并未解决正负极混合粉料中锌、镍的高效分离问题,且均未实现锌和镍的无萃取分级回收

Benefits of technology

传统废旧镍锌电池回收工艺需将正负极混合粉料在无机酸体系中全部浸出,再通过多级萃取、反萃等繁琐操作实现镍与锌的分离。本发明依据镍和锌在有机酸体系中浸出行为的显著差异,通过两段浸出工艺实现选择性分级回收:第一段以有机酸选择性浸出锌,锌浸出率可达97%以上,而镍浸出率不超过1.5%;第二段以有机酸-无机酸混合体系浸出镍,镍浸出率可达80%以上。全程无需萃取操作,突破了传统湿法冶金对萃取工艺的依赖,大幅简化了分离流程。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of battery material recycling technology, specifically relating to a graded recycling method for positive and negative electrode materials of nickel-zinc batteries, the recycled materials obtained, and their applications. Based on the significant differences in the leaching behavior of nickel and zinc in organic acid systems, this invention achieves selective graded recycling through a two-stage leaching process: the first stage selectively leaches zinc with organic acids, achieving a zinc leaching rate of over 97%, while the nickel leaching rate is less than 1.5%; the second stage leaches nickel using a mixed organic-inorganic acid system, achieving a nickel leaching rate of over 80%. The entire process eliminates the need for extraction operations, breaking through the dependence of traditional hydrometallurgical processes on extraction techniques and significantly simplifying the separation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery material recycling technology, specifically relating to a graded recycling method for positive and negative electrode materials of nickel-zinc batteries, the recycled materials obtained, and their applications. Background Technology

[0002] Among aqueous batteries, nickel-zinc batteries have gradually replaced some lithium-ion batteries due to their advantages such as high safety, high output voltage, high power density, high energy density, and environmental friendliness. Nickel-zinc batteries have demonstrated significant advantages in numerous fields, and their industrialization is continuously advancing. With the rapid expansion of the market, the resource utilization and harmless disposal of retired nickel-zinc batteries urgently needs to be considered. Nickel-zinc battery materials contain high-value metals such as nickel, cobalt, and zinc, offering considerable economic benefits. Although they themselves do not contain highly toxic heavy metals such as lead, cadmium, and mercury, improper disposal can still harm soil and water bodies.

[0003] Aqueous nickel-zinc batteries consist of a positive electrode, a negative electrode, and an electrolyte. The positive electrode is Ni(OH)₂ / NiOOH, the negative electrode is ZnO / Zn, and the electrolyte is KOH and additives. Nickel-zinc batteries use nickel foam as the current collector for the positive electrode, while the negative electrode current collector directly uses commercial zinc or copper sheets / mesh. The separator typically uses a secondary separator (non-woven fabric and cellulose) in combination with a primary separator (composed of fibers with strong antioxidant properties and polymers). Current research on nickel-zinc battery recycling mainly focuses on leaching and product regeneration after the positive or negative electrode is separated. However, in actual production, the batteries are mostly crushed and sorted to obtain a mixed powder of positive and negative electrodes.

[0004] Currently, the wet extraction of valuable metals from spent nickel-zinc batteries mainly employs an inorganic acid-hydrogen peroxide system. After leaching the valuable metals, processes such as impurity removal, extraction, and back-extraction are required, making the process quite cumbersome. For example, existing technology discloses a method for recovering valuable metals from spent nickel-zinc batteries. This method involves self-discharge treatment, crushing, and magnetic separation of the spent nickel-zinc batteries to obtain a mixture that passes through a sieve. The mixture is then leached with sulfuric acid, and the leachate is subjected to impurity removal and extraction to ultimately obtain a binary mixed salt of nickel sulfate and cobalt sulfate, calcium chloride hexahydrate, and zinc sulfate or zinc chloride heptahydrate. The aforementioned existing technology uses inorganic acid to leach all metals followed by extraction separation, resulting in a lengthy process, and the use of inorganic acids and extractants poses significant environmental hazards.

[0005] In addition, some studies have attempted to recycle spent nickel-zinc batteries using organic acids. Existing technology discloses a method for regenerating cathode materials from retired nickel-zinc batteries and the resulting regenerated cathode materials. This method involves leaching the cathode material with organic acids and adjusting the nickel-cobalt ratio to prepare nickel-cobalt hydroxide. However, the aforementioned organic acid leaching schemes are all designed for single electrode materials and do not solve the problem of efficient separation of zinc and nickel in mixed cathode and anode powders, nor do they achieve extraction-free fractional recovery of zinc and nickel.

[0006] It can be seen that the existing technologies for recycling the positive and negative electrode mixed powder of nickel-zinc batteries generally have the following shortcomings: (1) Inorganic acid is mainly used to leach out all metal ions, and then the separation between metals is achieved through impurity removal, multi-stage extraction and other means. The process is complicated and the cost is high; (2) The use of inorganic acid and extractant is not environmentally friendly and generates the risk of secondary pollution; (3) Organic acid leaching and non-extraction graded recycling technology for positive and negative electrode mixed powder is still blank. Summary of the Invention

[0007] The purpose of this invention is to provide a graded recycling method for positive and negative electrode materials of nickel-zinc batteries, the recycled materials obtained, and their applications.

[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a graded recycling method for positive and negative electrode materials of nickel-zinc batteries, comprising the following steps: The positive and negative electrode sheets obtained from the dismantling of waste nickel-zinc batteries are calcined separately, and the calcined materials are mixed to obtain a positive and negative electrode mixed powder. The positive and negative electrode mixed powders are placed in an organic acid solution for a first-stage leaching to obtain a zinc-containing leaching solution and a nickel-containing leaching residue. The organic acid used in the first-stage leaching includes at least one of acetic acid, citric acid, malic acid, and tartaric acid. The first-stage leaching is carried out under ultrasonic conditions at a temperature of 5-60°C for a time of 30-180 minutes. The nickel-containing leaching residue is placed in a mixed acid solution of organic and inorganic acids for a second leaching stage to obtain a nickel-containing leaching solution; the organic acid used in the second leaching stage includes at least one of acetic acid, citric acid, malic acid and tartaric acid, and the inorganic acid includes at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid and aminosulfonic acid. Regenerated zinc oxide and recycled nickel oxide are recovered from the zinc-containing leachate and the nickel-containing leachate, respectively.

[0009] Preferably, the calcination temperature is 400~600℃, the heating rate is 1~20℃ / min, and the holding time is 1~4h.

[0010] Preferably, in the first leaching stage, the concentration of the organic acid is 0.01~5 mol / L; The solid-liquid ratio of the first leaching stage is 5~50g / L.

[0011] Preferably, in the second leaching stage, the concentration of the organic acid is 0.5~5 mol / L; and the volume of the inorganic acid is 1~10% of the total volume of the mixed acid solution. The solid-liquid ratio of the second leaching stage is 10~80g / L; The second leaching stage is carried out at a temperature of 65~105℃ for a time of 30~180min; the second leaching stage is carried out under stirring conditions, and the stirring speed is 100~1000rpm.

[0012] Preferably, the recycling process of the recycled zinc oxide is as follows: the pH of the zinc-containing leachate is adjusted to 3.5-5, a surfactant is added, and oxalic acid solution is added dropwise under stirring to carry out a precipitation reaction. The pH of the system is maintained at 3.5-4, and the obtained precipitate is calcined to obtain recycled zinc oxide.

[0013] Preferably, the surfactant includes at least one selected from polyvinylpyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate; The zinc content in the zinc-containing leachate is 10-15 g / L; the amount of surfactant added is 0.1-0.5 g / L. The molar ratio of oxalic acid in the oxalic acid solution to zinc ions in the zinc-containing leachate is 1.05~1.2:1; The precipitation reaction is carried out at a temperature of 25~60℃ for a time of 30~180 min; The calcination temperature is 400~500℃, and the time is 1~4h.

[0014] Preferably, the recycling process of the recycled nickel oxide is as follows: the pH of the nickel-containing leaching solution is adjusted to 5-7, a surfactant is added, oxalic acid solution is added dropwise under stirring conditions, precipitation reaction and aging are carried out in sequence, and the obtained precipitate is calcined to obtain recycled nickel oxide.

[0015] Preferably, the surfactant includes at least one selected from polyvinylpyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate; The nickel content in the nickel-containing leachate is 9-15 g / L; the amount of surfactant added is 0.1-0.5 g / L. The molar ratio of oxalic acid in the oxalic acid solution to nickel ions in the nickel-containing leachate is 1.05~1.2:1; The precipitation reaction is carried out at a temperature of 25~60℃ for a time of 30~180 min; The aging time is 1-5 hours; The calcination temperature is 400~600℃, and the time is 1~4h.

[0016] The present invention also provides a recycled material obtained by the graded recycling method described in the above technical solution.

[0017] The present invention also provides the use of the recycled materials described in the above technical solutions in nickel-zinc batteries, supercapacitors, or perovskite solar cells.

[0018] Compared with the prior art, the beneficial effects of the present invention include: (1) Achieving efficient fractional separation of nickel and zinc under extraction-free conditions. Traditional recycling processes for spent nickel-zinc batteries require the complete leaching of the positive and negative electrode powders in an inorganic acid system, followed by cumbersome operations such as multi-stage extraction and back-extraction to separate nickel and zinc. This invention, based on the significant differences in the leaching behavior of nickel and zinc in organic acid systems, achieves selective and graded recovery through a two-stage leaching process: the first stage selectively leaches zinc with organic acids, achieving a zinc leaching rate of over 97%, while the nickel leaching rate is less than 1.5%; the second stage leaches nickel using a mixed organic-inorganic acid system, achieving a nickel leaching rate of over 80%. The entire process eliminates the need for extraction operations, breaking through the dependence of traditional hydrometallurgical processes on extraction and significantly simplifying the separation process.

[0019] (ii) The process is green and environmentally friendly, and the environmental hazards are significantly reduced. Existing technologies mostly employ inorganic acid systems such as sulfuric acid-hydrogen peroxide for leaching, and use organic extractants such as P507 and solvents such as sulfonated kerosene during the extraction process, resulting in large amounts of wastewater and a heavy environmental burden. This invention uses organic acids as the primary leaching agent throughout the entire process. Organic acids are biodegradable, have low corrosivity, and low toxicity, posing a far lower environmental hazard than inorganic acids. Furthermore, the recovery process does not involve the use of extractants or toxic organic solvents, resulting in minimal wastewater generation, aligning with the development trends of green chemistry and a circular economy.

[0020] (iii) Short process flow and low production cost Compared to existing technologies that require lengthy processes such as leaching, impurity removal, multi-stage extraction, concentration, and crystallization, this invention only requires two stages of leaching and precipitation-calcination to obtain the regenerated product, eliminating the need for extraction and back-extraction equipment and reagents. The process is significantly shortened, and equipment investment and operating costs are greatly reduced, facilitating the large-scale industrial application of the technology.

[0021] (iv) The product has high purity and controllable morphology, and can be directly reused. This invention uses zinc-containing and nickel-containing leaching solutions as raw materials, employing oxalic acid precipitation combined with surfactant regulation, and calcining to obtain recycled zinc oxide and recycled nickel oxide with good crystal structure and controllable morphology. The recycled materials have high purity and can be directly applied to nickel-zinc batteries, supercapacitors, perovskite solar cells, and other fields, realizing a closed-loop recycling from waste batteries to battery materials, with considerable economic benefits and strategic resource value.

[0022] (v) Balancing resource recovery rate and separation selectivity Existing technologies, when pursuing high metal leaching rates, often struggle to achieve effective separation, necessitating subsequent impurity removal processes. This invention, by precisely controlling the first-stage leaching parameters, effectively suppresses nickel leaching while ensuring a high zinc leaching rate, achieving in-situ separation of zinc and nickel. The second stage utilizes a synergistic leaching process of organic and inorganic acids, achieving a nickel leaching rate of up to 94.8%, balancing high recovery rate and high selectivity, resulting in overall resource utilization superior to traditional processes. Attached Figure Description

[0023] Figure 1 This is a process flow diagram of the present invention; Figure 2 The image shows the XRD pattern of the regenerated zinc oxide obtained in Example 1. Figure 3 Here is a SEM image of the regenerated zinc oxide obtained in Example 1; Figure 4 Here is a SEM image of the regenerated zinc oxide obtained in Example 3; Figure 5 The image shows the XRD pattern of the recycled nickel oxide obtained in Example 1. Figure 6 Here is a SEM image of the recycled nickel oxide obtained in Example 1; Figure 7 This is a SEM image of the recycled nickel oxide obtained in Example 3. Detailed Implementation

[0024] Figure 1 The process flow diagram provided by this invention is described below in conjunction with... Figure 1 The technical solution of the present invention will be described in detail.

[0025] This invention provides a graded recycling method for positive and negative electrode materials of nickel-zinc batteries, comprising the following steps: The positive and negative electrode sheets obtained from the dismantling of waste nickel-zinc batteries are calcined separately, and the calcined materials are mixed to obtain a positive and negative electrode mixed powder. The positive and negative electrode mixed powders are placed in an organic acid solution for a first-stage leaching to obtain a zinc-containing leaching solution and a nickel-containing leaching residue. The organic acid used in the first-stage leaching includes at least one of acetic acid, citric acid, malic acid, and tartaric acid. The first-stage leaching is carried out under ultrasonic conditions at a temperature of 5-60°C for a time of 30-180 minutes. The nickel-containing leaching residue is placed in a mixed acid solution of organic and inorganic acids for a second leaching stage to obtain a nickel-containing leaching solution; the organic acid used in the second leaching stage includes at least one of acetic acid, citric acid, malic acid and tartaric acid, and the inorganic acid includes at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid and aminosulfonic acid. Regenerated zinc oxide and recycled nickel oxide are recovered from the zinc-containing leachate and the nickel-containing leachate, respectively.

[0026] This invention involves dismantling waste nickel-zinc batteries to obtain positive and negative electrode sheets, which are then calcined separately. The calcined materials are then mixed to obtain a mixed positive and negative electrode powder.

[0027] The present invention does not impose any special limitations on the disassembly process; any process known to those skilled in the art can be used.

[0028] In this invention, the calcination temperature is preferably 400~600℃ (specifically 400℃, 500℃, 600℃), the heating rate is preferably 1~20℃ / min (specifically 1℃ / min, 5℃ / min, 10℃ / min, 15℃ / min, 20℃ / min), and the holding time is preferably 1~4h (specifically 1h, 2h, 3h, 4h); the calcination is preferably carried out in an air atmosphere; the binder and conductive agent are removed by calcination; the calcination process also preferably includes separation; and the mixing method is preferably grinding and mixing.

[0029] After obtaining the positive and negative electrode mixed powder, the present invention places the positive and negative electrode mixed powder in an organic acid solution for a first stage of leaching to obtain a zinc-containing leaching solution and a nickel-containing leaching residue.

[0030] In this invention, the organic acid used in the first leaching stage includes at least one selected from acetic acid, citric acid, malic acid, and tartaric acid; the concentration of the organic acid is preferably 0.01~5 mol / L (specifically, it can be 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, or 5 mol / L); the solid-liquid ratio of the first leaching stage is preferably 5~50 g / L (specifically, it can be 5 g / L, 10 g / L, 15 g / L, or 20 g / L). The concentrations of nickel in the leaching solution are 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, and 50 g / L. The first stage of leaching is carried out under ultrasonic conditions at a temperature of 5-60℃ (specifically, 5℃, 10℃, 15℃, 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, and 60℃) for a time of 30-180 min (specifically, 30 min, 60 min, 90 min, 120 min, 150 min, and 180 min). After the first stage of leaching, it is preferable to further include vacuum filtration and hot water rinsing, and to dry the resulting nickel-containing leaching residue at a temperature preferably 80℃.

[0031] After obtaining the nickel-containing leaching residue, the present invention places the nickel-containing leaching residue in a mixed acid solution of organic acid and inorganic acid for a second leaching stage to obtain a nickel-containing leaching solution.

[0032] In this invention, the organic acid used in the second stage of leaching includes at least one selected from acetic acid, citric acid, malic acid, and tartaric acid; the inorganic acid includes at least one selected from sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, and aminosulfonic acid; the concentration of the organic acid is preferably 0.5~5 mol / L (specifically, it can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, or 5 mol / L); the mass concentration of the sulfuric acid is preferably 98%; the volume of the inorganic acid is preferably 1~10% of the total volume of the mixed acid solution (specifically, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%); the solid-liquid ratio of the second stage of leaching is preferably 10. The concentration of the second leaching stage is preferably 80 g / L (specifically, it can be 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, or 80 g / L); the preferred leaching temperature for the second stage is 65-105℃ (specifically, it can be 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, or 105℃), and the preferred leaching time is 30-180 min (specifically, it can be 30 min, 60 min, 90 min, 120 min, 150 min, or 180 min); the second leaching stage is preferably carried out under stirring conditions, and the stirring speed is preferably 100-1000 rpm (specifically, it can be 100 rpm, 500 rpm, or 1000 rpm); after the second leaching stage, vacuum filtration is also preferably performed.

[0033] After obtaining the zinc-containing leachate and the nickel-containing leachate, the present invention recovers recycled zinc oxide and recycled nickel oxide from the zinc-containing leachate and the nickel-containing leachate, respectively.

[0034] Before the recycling, the present invention preferably includes measuring the zinc content in the zinc-containing leachate and the nickel content in the nickel-containing leachate, and calculating the corresponding leaching rate according to the following formula; Formula 1; Where η% is the metal leaching rate; m is the mass of the raw material (positive and negative electrode mixture); W% is the metal content in the raw material; V is the volume of the leachate; and C is the metal concentration in the leachate.

[0035] In this invention, the measurement is preferably performed using an inductively coupled plasma optical emission spectrometer (ICP-OES).

[0036] In this invention, the zinc content in the zinc-containing leachate is preferably 10-15 g / L, and the zinc leaching rate is preferably 97-99.99%; the nickel content is preferably 0.01-1 g / L, and the nickel leaching rate is preferably 0.5-1.5%.

[0037] In this invention, the nickel content in the nickel-containing leachate is preferably 9-15 g / L, and the nickel leaching rate is preferably 80-99%.

[0038] In this invention, the preferred process for recovering the recycled zinc oxide is as follows: the pH of the zinc-containing leaching solution is adjusted to 3.5-5 (specifically, it can be 3.5, 4, 4.5, or 5), a surfactant is added, and oxalic acid solution is added dropwise under stirring to carry out a precipitation reaction. The pH of the system is maintained at 3.5-4, and the obtained precipitate is calcined to obtain recycled zinc oxide.

[0039] In this invention, the reagent used to adjust the pH value is preferably at least one of ammonia, sodium carbonate solution, and sodium bicarbonate solution. In this invention, the surfactant preferably includes at least one of polyvinylpyrrolidone (PVP), polyethylene glycol, hexadecyltrimethylammonium bromide (CTAB), and sodium dodecyl sulfate; the amount of surfactant added is preferably 0.1~0.5 g / L (specifically, 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, or 0.5 g / L); the molar ratio of oxalic acid in the oxalic acid solution to zinc ions in the zinc-containing leaching solution is preferably 1.05~1.2:1 (specifically, 1.05:1, 1.1:1, 1.15:1, or 1.2:1); the reagent used to maintain the pH value of the system is preferably ammonia; the preferred temperature for the precipitation reaction is... The calcination temperature is preferably 25~60℃ (more preferably room temperature), and the time is preferably 30~180min (specifically 30min, 60min, 90min, 120min, 150min, 180min; the precipitation reaction occurs during the dropwise addition of oxalic acid solution, and the reaction time here does not include the time for adding oxalic acid, that is, it refers to the reaction time after the dropwise addition is completed); after the precipitation reaction, it is also preferred to wash and dry the obtained precipitate; the calcination temperature is preferably 400~500℃ (specifically 400℃, 450℃, 500℃), and the time is preferably 1~4h (specifically 1h, 2h, 3h, 4h); the calcination is preferably carried out in an air atmosphere.

[0040] In this invention, the preferred process for recovering the recycled nickel oxide is as follows: the pH of the nickel-containing leaching solution is adjusted to 5-7 (specifically, it can be 5, 5.5, 6, 6.5, or 7), a surfactant is added, oxalic acid solution is added dropwise under stirring conditions, precipitation reaction and aging are carried out in sequence, and the obtained precipitate is calcined to obtain recycled nickel oxide.

[0041] In this invention, the reagent used to adjust the pH value is preferably at least one of ammonia, sodium carbonate solution, and sodium bicarbonate solution; the surfactant preferably includes at least one of polyvinylpyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate; the amount of surfactant added is preferably 0.1~0.5 g / L (specifically, it can be 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, or 0.5 g / L); the molar ratio of oxalic acid in the oxalic acid solution to nickel ions in the nickel-containing leaching solution is preferably 1.05~1.2:1 (specifically, it can be 1.05:1, 1.1:1, 1.15:1, or 1.2:1); the temperature of the precipitation reaction is preferably 25~60℃ (more preferably room temperature), and the time is preferably 30~180 min. (Specifically, the time can be 30 min, 60 min, 90 min, 120 min, 150 min, or 180 min; the precipitation reaction occurs during the dropwise addition of oxalic acid solution, and the reaction time here does not include the time for adding oxalic acid, i.e., it refers to the reaction time after the addition is completed); the aging time is preferably 1-5 h (specifically, 1 h, 2 h, 3 h, 4 h, or 5 h); the aging process preferably includes washing and drying the obtained precipitate, and the washing is preferably performed sequentially with deionized water and ethanol; the calcination temperature is preferably 400-600℃ (specifically, 400℃, 450℃, 500℃, 550℃, or 600℃), and the time is preferably 1-4 h (specifically, 1 h, 2 h, 3 h, or 4 h); the calcination is preferably carried out in an air atmosphere.

[0042] The present invention also provides a recycled material obtained by the graded recycling method described in the above technical solution.

[0043] The present invention also provides the use of the recycled materials described in the above technical solutions in nickel-zinc batteries, supercapacitors, or perovskite solar cells.

[0044] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.

[0045] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0046] Example 1 After disassembling the waste nickel-zinc batteries, the positive and negative electrode sheets are separated. The temperature is raised to 500°C in air at a heating rate of 10°C / min and held for 2 hours to remove the binder and conductive agent, and the positive and negative electrode powders are separated. Then, the positive and negative electrode powders are ground and mixed evenly with an agate mortar to obtain a positive and negative electrode mixed powder. The positive and negative electrode mixed powders were ultrasonically dispersed in a 0.5 mol / L citric acid solution at a solid-liquid ratio of 30 g / L for 30 min at a constant temperature of 25℃. After the reaction was completed, the mixture was vacuum filtered and rinsed with a small amount of hot water. The zinc-containing leaching solution and the nickel-containing leaching residue were collected. The nickel-containing leaching residue was then dried in a forced-air drying oven at 80℃. Add 98wt% sulfuric acid (2.5% of the total volume) to 2mol / L citric acid to obtain a mixed acid solution. Add dried nickel-containing leaching residue to the mixed acid solution at a solid-liquid ratio of 50g / L and stir for 2 hours at a speed of 600rpm and a reaction temperature of 95℃. After the reaction is completed, filter under vacuum and collect the nickel-containing leaching solution. ICP-OES tests were performed on the zinc-containing and nickel-containing leachates, and calculations based on Formula 1 showed that the zinc content in the zinc-containing leachate was 13.5 g / L, with a leaching rate of 97.1%, and the nickel content was 0.08 g / L, with a leaching rate of 1.2%; the nickel content in the nickel-containing leachate was 9.6 g / L, with a leaching rate of 80%. The pH of the zinc leaching solution was adjusted to 4 with ammonia water, and 0.2 g / L of CTAB was added. Oxalic acid solution (with a molar ratio of oxalic acid to zinc ions of 1.1:1) was slowly added dropwise while stirring at room temperature, while maintaining the pH of the system at 4. After the addition was completed, the solution was stirred for 1 hour, then washed and dried. Finally, the solution was calcined in a muffle furnace at 450°C in air for 2 hours to obtain regenerated zinc oxide. The pH of the nickel-containing leaching solution was adjusted to 5.5 with ammonia water, and then 0.2 g / L of CTAB was added. Oxalic acid solution (with a molar ratio of oxalic acid to nickel ions of 1.1:1) was slowly added dropwise to the nickel-containing leaching solution at room temperature with stirring. After the addition was completed, the solution was stirred for 1 h. After the reaction was completed, the solution was aged for 2 h, washed with deionized water and ethanol, and dried. Finally, the dried sample was placed in a muffle furnace and calcined at 450 °C in air for 2 h to obtain regenerated nickel oxide.

[0047] Example 2 After disassembling the waste nickel-zinc batteries, the positive and negative electrode sheets are separated. The temperature is raised to 500°C in air at a heating rate of 10°C / min and held for 2 hours to remove the binder and conductive agent, and the positive and negative electrode powders are separated. Then, the positive and negative electrode powders are ground and mixed evenly with an agate mortar to obtain a positive and negative electrode mixed powder. The positive and negative electrode mixed powders were ultrasonically dispersed in a 0.5 mol / L citric acid solution for 30 min at a solid-liquid ratio of 20 g / L, with the temperature kept constant at 25℃. After the reaction was completed, the mixture was vacuum filtered and rinsed with a small amount of hot water. The zinc-containing leaching solution and the nickel-containing leaching residue were collected. The nickel-containing leaching residue was then placed in a forced-air drying oven and dried at 80℃. Add 98wt% sulfuric acid (5% of the total volume) to 2mol / L citric acid to obtain a mixed acid solution. Add dried nickel-containing leaching residue to the mixed acid solution at a solid-liquid ratio of 50g / L and stir for 2 hours at a speed of 600rpm and a reaction temperature of 95℃. After the reaction is completed, filter under vacuum and collect the nickel-containing leaching solution. ICP-OES tests were performed on the zinc-containing and nickel-containing leachates, and calculations based on Formula 1 showed that the zinc content in the zinc-containing leachate was 13.7 g / L, with a leaching rate of 98.3%, and the nickel content was 0.07 g / L, with a leaching rate of 0.96%; the nickel content in the nickel-containing leachate was 10.4 g / L, with a leaching rate of 87.1%. The pH of the zinc leaching solution was adjusted to 4 with ammonia water, and 0.3 g / L of CTAB was added. Oxalic acid solution (with a molar ratio of oxalic acid to zinc ions of 1.1:1) was slowly added dropwise while stirring at room temperature, while maintaining the pH of the system at 4. After the addition was completed, the solution was stirred for 2 hours, then washed and dried. Finally, the solution was calcined in a muffle furnace at 450°C in air for 3 hours to obtain regenerated zinc oxide. The pH of the nickel-containing leaching solution was adjusted to 5.5 with ammonia water, and then 0.3 g / L of CTAB was added. Oxalic acid solution (with a molar ratio of oxalic acid to nickel ions of 1.1:1) was slowly added dropwise to the nickel-containing leaching solution at room temperature with stirring. After the addition was completed, the solution was stirred for 2 hours. After the reaction was completed, the solution was aged for 2 hours, washed with deionized water and ethanol, and dried. Finally, the dried sample was placed in a muffle furnace and calcined at 450°C in air for 3 hours to obtain regenerated nickel oxide.

[0048] Example 3 After disassembling the waste nickel-zinc batteries, the positive and negative electrode sheets are separated. The temperature is raised to 500°C in air at a heating rate of 10°C / min and held for 2 hours to remove the binder and conductive agent, and the positive and negative electrode powders are separated. Then, the positive and negative electrode powders are ground and mixed evenly with an agate mortar to obtain a positive and negative electrode mixed powder. The positive and negative electrode mixed powders were ultrasonically dispersed in a 1 mol / L citric acid solution at a solid-liquid ratio of 30 g / L for 30 min at a constant temperature of 25℃. After the reaction was completed, the mixture was vacuum filtered and rinsed with a small amount of hot water. The zinc-containing leaching solution and the nickel-containing leaching residue were collected. The nickel-containing leaching residue was then placed in a forced-air drying oven and dried at 80℃. Add 98wt% sulfuric acid (7% of the total volume) to 2mol / L citric acid to obtain a mixed acid solution. Add dried nickel-containing leaching residue to the mixed acid solution at a solid-liquid ratio of 50g / L and stir for 2 hours at a speed of 600rpm and a reaction temperature of 95℃. After the reaction is completed, filter under vacuum and collect the nickel-containing leaching solution. ICP-OES tests were performed on the zinc-containing and nickel-containing leachates, and calculations based on Formula 1 showed that the zinc content in the zinc-containing leachate was 13.8 g / L, with a leaching rate of 98.9%, and the nickel content was 0.09 g / L, with a leaching rate of 1.33%; the nickel content in the nickel-containing leachate was 11.4 g / L, with a leaching rate of 94.8%. The pH of the zinc leaching solution was adjusted to 4 using sodium carbonate solution. 0.2 g / L of PVP was added, and oxalic acid solution (with a molar ratio of oxalic acid to zinc ions of 1.1:1) was slowly added dropwise while stirring at room temperature, while maintaining the pH of the system at 4. After the addition was completed, the solution was stirred for 2 h, then washed and dried. Finally, the solution was calcined in a muffle furnace at 450 °C in air for 2 h to obtain regenerated zinc oxide. The pH of the nickel-containing leaching solution was adjusted to 5.5 using sodium carbonate solution. Then, 0.2 g / L of PVP was added. Oxalic acid solution (with a molar ratio of oxalic acid to nickel ions of 1.1:1) was slowly added dropwise to the nickel-containing leaching solution at room temperature with stirring. After the addition was complete, the solution was stirred for 3 hours. After the reaction was completed, the solution was aged for 2 hours. The solution was washed with deionized water and ethanol and dried. Finally, the dried sample was placed in a muffle furnace and calcined at 450°C in air for 2 hours to obtain regenerated nickel oxide.

[0049] Example 4 After disassembling the waste nickel-zinc batteries, the positive and negative electrode sheets are separated. The temperature is raised to 500°C in air at a heating rate of 10°C / min and held for 2 hours to remove the binder and conductive agent, and the positive and negative electrode powders are separated. Then, the positive and negative electrode powders are ground and mixed evenly with an agate mortar to obtain a positive and negative electrode mixed powder. The positive and negative electrode mixed powders were ultrasonically dispersed in a 1 mol / L citric acid solution at a solid-liquid ratio of 30 g / L for 60 min at a constant temperature of 25℃. After the reaction was completed, the mixture was vacuum filtered and rinsed with a small amount of hot water. The zinc-containing leaching solution and the nickel-containing leaching residue were collected. The nickel-containing leaching residue was then placed in a forced-air drying oven and dried at 80℃. Add 98wt% sulfuric acid (2.5% of the total volume) to 2mol / L citric acid to obtain a mixed acid solution. Add dried nickel-containing leaching residue to the mixed acid solution at a solid-liquid ratio of 50g / L and stir for 2 hours at a speed of 600rpm and a reaction temperature of 95℃. After the reaction is completed, filter under vacuum and collect the nickel-containing leaching solution. ICP-OES tests were performed on the zinc-containing and nickel-containing leachates, and calculations based on Formula 1 showed that the zinc content in the zinc-containing leachate was 13.9 g / L, with a leaching rate of 99.6%, and the nickel content was 0.09 g / L, with a leaching rate of 1.31%; the nickel content in the nickel-containing leachate was 11.1 g / L, with a leaching rate of 92.7%. The pH of the zinc leaching solution was adjusted to 4 using sodium carbonate solution. 0.3 g / L of PVP was added, and oxalic acid solution (with a molar ratio of oxalic acid to zinc ions of 1.1:1) was slowly added dropwise while stirring at room temperature, while maintaining the pH of the system at 4. After the addition was completed, the solution was stirred for 2 hours, then washed and dried. Finally, the solution was calcined in a muffle furnace at 500°C in air for 2 hours to obtain regenerated zinc oxide. The pH of the nickel-containing leaching solution was adjusted to 5.5 using sodium carbonate solution. Then, 0.3 g / L of PVP was added. Oxalic acid solution (with a molar ratio of oxalic acid to nickel ions of 1.1:1) was slowly added dropwise to the nickel-containing leaching solution at room temperature with stirring. After the addition was complete, the solution was stirred for 4 hours. After the reaction was completed, the solution was aged for 2 hours. The solution was washed with deionized water and ethanol and dried. Finally, the dried sample was placed in a muffle furnace and calcined at 500°C in air for 2 hours to obtain regenerated nickel oxide.

[0050] Comparative Example 1 After disassembling the waste nickel-zinc batteries, the positive and negative electrode sheets are separated. The temperature is raised to 500°C in air at a heating rate of 10°C / min and held for 2 hours to remove the binder and conductive agent, and the positive and negative electrode powders are separated. Then, the positive and negative electrode powders are ground and mixed evenly with an agate mortar to obtain a positive and negative electrode mixed powder. The positive and negative electrode mixed powders were ultrasonically dispersed in a 1 mol / L citric acid solution at a solid-liquid ratio of 30 g / L for 60 min at a constant temperature of 25℃. After the reaction was completed, the mixture was vacuum filtered and rinsed with a small amount of hot water. The zinc-containing leaching solution and the nickel-containing leaching residue were collected. The nickel-containing leaching residue was then placed in a forced-air drying oven and dried at 80℃. The dried nickel-containing leaching residue was stirred in 2 mol / L citric acid at a solid-liquid ratio of 50 g / L for 2 h at a speed of 600 rpm and a reaction temperature of 95 °C. After the reaction was completed, the residue was filtered under vacuum and the nickel-containing leaching solution was collected. ICP-OES tests were performed on the zinc-containing and nickel-containing leachates, and calculations based on Formula 1 showed that the zinc content in the zinc-containing leachate was 13.9 g / L, with a leaching rate of 99.6%, and the nickel content was 0.09 g / L, with a leaching rate of 1.31%; the nickel content in the nickel-containing leachate was 8.1 g / L, with a leaching rate of 67.8%. The pH of the zinc leaching solution was adjusted to 4 using sodium carbonate solution. Oxalic acid solution (with a molar ratio of oxalic acid to zinc ions of 1.1:1) was slowly added dropwise while stirring at room temperature, while maintaining the pH of the system at 4. After the addition was completed, the solution was stirred for 2 hours, then washed and dried. Finally, the solution was calcined in a muffle furnace at 500°C in air for 2 hours to obtain regenerated zinc oxide. The pH of the nickel-containing leaching solution was adjusted to 5.5 using sodium carbonate solution. Oxalic acid solution (with a molar ratio of oxalic acid to nickel ions of 1.1:1) was slowly added dropwise to the nickel-containing leaching solution at room temperature and with stirring. After the addition was completed, the solution was stirred for 4 hours. After the reaction was completed, the solution was aged for 2 hours, washed with deionized water and ethanol, and dried. Finally, the dried sample was placed in a muffle furnace and calcined at 500°C in air for 2 hours to obtain regenerated nickel oxide.

[0051] Performance testing Test Example 1 Figure 2 The image shows the XRD pattern of the regenerated zinc oxide obtained in Example 1. Figure 2 It can be seen that the diffraction peaks of the regenerated zinc oxide are sharp and free of impurity peaks. The peak positions and peak intensities are perfectly matched with the zinc oxide standard card (PDF#36-1451), indicating that the zinc oxide prepared by this method has high purity. Figure 3 The image shows a SEM image of the regenerated zinc oxide obtained in Example 1. Figure 3 It can be seen that when CTAB is used as a surfactant, the regenerated zinc oxide exhibits a microscopic morphology of micron-sized rod-shaped and needle-shaped aggregates. Figure 4 The image shows a SEM image of the regenerated zinc oxide obtained in Example 3. Figure 4 It can be seen that when PVP is used as a surfactant, the regenerated zinc oxide exhibits a microstructure of nano-sized spherical aggregates; compared with... Figure 3 and Figure 4 This indicates that the type of surfactant has a significant impact on the morphology of the product during the zinc oxide regeneration process, which enables the controllable preparation of the regenerated product. Figure 5 The image shows the XRD pattern of the recycled nickel oxide obtained in Example 1. Figure 5 It can be seen that the diffraction peaks of the recycled nickel oxide are sharp and free of impurity peaks. The peak positions and peak intensities are perfectly matched with the nickel oxide standard card (PDF#47-1049), indicating that the nickel oxide prepared by this method has high purity. Figure 6 The image shows a SEM image of the recycled nickel oxide obtained in Example 1. Figure 6 It can be seen that when CTAB is used as a surfactant, nickel oxide exhibits a microstructure of micron-sized rod-shaped aggregates. Figure 7 The image shows a SEM image of the recycled nickel oxide obtained in Example 3. Figure 7 It can be seen that when PVP is used as a surfactant, nickel oxide exhibits a microstructure of nano-sized spherical aggregates; compared with Figure 6 and Figure 7 This indicates that the type of surfactant has a significant impact on the morphology of the product during the nickel oxide regeneration process, which enables the controllable preparation of the regenerated product.

[0052] Test Example 2 The recycled materials obtained in the examples were assembled into pouch cells; The specific assembly process is as follows: the negative electrode is prepared using ZnO nanoparticles containing a small amount of zinc powder (regenerated ZnO: 85wt%; zinc powder 5wt%); conductive carbon black is used as a conductive agent (5wt%); sodium carboxymethyl cellulose (CMC, 2wt%) and styrene-butadiene rubber (SBR, 3wt%) are used as binders to form a uniform slurry, which is then coated onto the copper current collector; The positive electrode is prepared by mixing recycled nickel oxide (recycled NiO, 80wt%), nickel powder (12wt%) and a 60% polytetrafluoroethylene aqueous dispersion (PTFE, 8wt%), and adding an appropriate amount of deionized water to form a slurry; the prepared slurry is coated on a nickel foam substrate and then dried at 80°C for 1 hour; The diaphragm adopts a composite double-layer structure: a non-woven fabric diaphragm facing the positive electrode and a microporous polypropylene (PP) diaphragm facing the negative electrode; the electrolyte is a 6.8M potassium hydroxide solution.

[0053] Battery performance test parameters: All prepared nickel-zinc batteries need to be activated for 2-3 cycles: constant current charging at 0.1C to 1.9V, followed by constant voltage charging at 1.9V to the cutoff current of 0.02C, and then resting for 10 minutes after charging is completed; then constant current discharge at 0.1C to 1.2V, and then resting for 10 minutes after discharge.

[0054] Electrochemical tests were conducted after activation. A constant current-constant voltage charge-constant current discharge mode was used: constant current charging at 0.2C to 1.9V, constant voltage at 1.9V until the current dropped to 0.01C, with a maximum charging time of 8 hours; after standing for 10 minutes, constant current discharge at 0.2C to 1.2V was performed. The ambient temperature was controlled at 25±2℃.

[0055] Table 1. Performance test results of batteries assembled from recycled materials obtained in the examples and comparative examples.

[0056] As shown in Table 1, both Examples 1 and 2 used CTAB as the surfactant in the preparation of the recycled product. Compared with Example 2, the amount of CTAB added in Example 2 was increased and the calcination time was prolonged, indicating that the amount of CTAB added and the calcination time have a significant impact on battery performance. Both Examples 3 and 4 used PVP as the surfactant in the preparation of the recycled product. Compared with Example 4, the amount of PVP added in Example 4 was increased and the calcination temperature was raised, indicating that the amount of PVP added and the calcination temperature have a significant impact on battery performance. Comparing Examples 1 and 3, the surfactants used in the preparation of the recycled product were CTAB and PVP, respectively, and the calcination parameters were the same. The electrical performance of Example 3 was significantly better than that of Example 1, indicating that the nanoscale spherical agglomerates regenerated using PVP exhibited better electrical performance than the micron-sized rod / needle-shaped agglomerates regenerated using CTAB.

[0057] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for graded recycling of positive and negative electrode materials for nickel-zinc batteries, characterized in that, Includes the following steps: The positive and negative electrode sheets obtained from the dismantling of waste nickel-zinc batteries are calcined separately, and the calcined materials are mixed to obtain a positive and negative electrode mixed powder. The positive and negative electrode mixed powders are placed in an organic acid solution for a first-stage leaching to obtain a zinc-containing leaching solution and a nickel-containing leaching residue. The organic acid used in the first-stage leaching includes at least one of acetic acid, citric acid, malic acid, and tartaric acid. The first-stage leaching is carried out under ultrasonic conditions at a temperature of 5-60°C for a time of 30-180 minutes. The nickel-containing leaching residue is placed in a mixed acid solution of organic and inorganic acids for a second leaching stage to obtain a nickel-containing leaching solution; the organic acid used in the second leaching stage includes at least one of acetic acid, citric acid, malic acid and tartaric acid, and the inorganic acid includes at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid and aminosulfonic acid. Regenerated zinc oxide and recycled nickel oxide are recovered from the zinc-containing leachate and the nickel-containing leachate, respectively.

2. The graded recycling method according to claim 1, characterized in that, The calcination temperature is 400~600℃, the heating rate is 1~20℃ / min, and the holding time is 1~4h.

3. The graded recycling method according to claim 1, characterized in that, In the first leaching stage, the concentration of the organic acid is 0.01~5 mol / L; The solid-liquid ratio of the first leaching stage is 5~50g / L.

4. The graded recycling method according to claim 1, characterized in that, In the second leaching stage, the concentration of the organic acid is 0.5~5 mol / L; the volume of the inorganic acid is 1~10% of the total volume of the mixed acid solution. The solid-liquid ratio of the second leaching stage is 10~80g / L; The second leaching stage is carried out at a temperature of 65~105℃ for a time of 30~180min; the second leaching stage is carried out under stirring conditions, and the stirring speed is 100~1000rpm.

5. The graded recycling method according to claim 1, characterized in that, The process for recovering the recycled zinc oxide is as follows: the pH of the zinc-containing leaching solution is adjusted to 3.5-5, a surfactant is added, and oxalic acid solution is added dropwise under stirring to carry out a precipitation reaction. The pH of the system is maintained at 3.5-4, and the obtained precipitate is calcined to obtain recycled zinc oxide.

6. The graded recycling method according to claim 5, characterized in that, The surfactant includes at least one of polyvinylpyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate; The zinc content in the zinc-containing leachate is 10-15 g / L; the amount of surfactant added is 0.1-0.5 g / L. The molar ratio of oxalic acid in the oxalic acid solution to zinc ions in the zinc-containing leachate is 1.05~1.2:1; The precipitation reaction is carried out at a temperature of 25~60℃ for a time of 30~180 min; The calcination temperature is 400~500℃, and the time is 1~4h.

7. The graded recycling method according to claim 1, characterized in that, The recycling process of the recycled nickel oxide is as follows: the pH of the nickel-containing leaching solution is adjusted to 5-7, a surfactant is added, and oxalic acid solution is added dropwise under stirring conditions. Precipitation reaction and aging are carried out in sequence, and the obtained precipitate is calcined to obtain recycled nickel oxide.

8. The graded recycling method according to claim 7, characterized in that, The surfactant includes at least one of polyvinylpyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate; The nickel content in the nickel-containing leachate is 9-15 g / L; the amount of surfactant added is 0.1-0.5 g / L. The molar ratio of oxalic acid in the oxalic acid solution to nickel ions in the nickel-containing leachate is 1.05~1.2:1; The precipitation reaction is carried out at a temperature of 25~60℃ for a time of 30~180 min; The aging time is 1-5 hours; The calcination temperature is 400~600℃, and the time is 1~4h.

9. A recycled material, characterized in that, Obtained by the graded recycling method according to any one of claims 1 to 8.

10. The recycled material of claim 9 in nickel-zinc batteries, supercapacitors, or perovskite solar cells.